Enzymatic hydrolysis of soybean protein using lactic acid bacteria - Aguirre, Laura Beatriz María (2008)
The proteolytic activity of 12 lactic acid bacteria (LAB) strains, assayed on soy protein extract at a temperature of 37 °C for 6 h, was evaluated by SDS-PAGE, reverse-phase HPLC and free-amino acid analyses. The results indicated that α- and α′-subunits of β-conglycinin were the preferred substrates for the majority of the LAB. Only a few strains exerted some action against the basic polypeptides of glycinin, this fraction was the least degraded of all soy protein fractions. Whole-cell suspensions of LAB used in this study generated hydrophilic and hydrophobic peptides from mainly soy protein fractions. RP-HPLC analyses indicated differences in the profiles of the hydrolysates, with several peaks decreasing in size and new peaks being formed. Three of the selected strains assayed increased the level of total free amino acids in the soy protein extract (SPE) and hydrolyzed principally essential amino acids and flavour precursor amino acids.